The Inhabited Forest: Approaches The Inhabited Forest: Approaches to the Ancestry of the Tikuna Community - Gutiérrez Quevedo, Marcela (2025)
In the face of historical injustices against the indigenous peoples of the Amazon, this interdisciplinary research highlights, on the one hand, structural violence, destructive-colonizing development models, and on the other, the challenges and practices of justice in an indigenous community such as the Tikuna indians of Colombia. This work of applied comprehensive restorative justice (participatory action, auto-ethnography and ethnography) is the continuation of five years of research that has been carried out in the Amazon territory and responds to the objectives of understanding the ways of inhabiting the world of the peoples who inhabit the  Amazon, in particular the Tikuna people, with the purpose of contributing to the knowledge of other systems and cultural models that can be more sustainable and that can generate models of environmental justice. This work stands out for its continuous work since 2020 and its academic results on: extinct legal pluralism inside prison walls; indigenous justice in a multidiverse and conflict-ridden world; weaving, knotting, and unraveling the social fabric in the Tikuna communities of the Colombian Amazon to explore, in the last period, the connections with environmental justice. This article concludes that Tikuna resist through cooperation, autonomy, and resistance to ecosystem diversity.